2017
DOI: 10.1136/bmjopen-2016-014768
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence and aetiologies of pulmonary hypertension in Africa: a systematic review and meta-analysis protocol

Abstract: IntroductionThere are no data summarising the epidemiology of pulmonary hypertension (PH) among adults residing in Africa. Establishment of accurate epidemiological data on PH in this region may guide decision-making toward interventions to curb the burden of PH in Africa. The aim of this systematic review is to determine the prevalence, incidence and aetiologies of PH among people residing in Africa.Methods and analysisThis systematic review and meta-analysis will follow the MOOSE guidelines for reporting. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Some have shown that central obesity and overweight increased the risk of hypertension and MetS in PWH as they do in the general population [9•], whereas others reported that nadir CD4 T cell counts were also associated with hypertension in European [35] and African [34•] PWH, a finding specific to HIV populations. In addition to HIVrelated inflammation and detrimental effects of ART on adipocyte health and lipid metabolism, specific components of the virus such as the negative factor (Nef) protein, transcription protein (Tat), and glycoprotein 120 may contribute to the link between MetS and hypertension in PWH, perhaps superimposed on individual genetic predisposition [36][37][38].…”
Section: Role Of Hypertensionmentioning
confidence: 99%
“…Some have shown that central obesity and overweight increased the risk of hypertension and MetS in PWH as they do in the general population [9•], whereas others reported that nadir CD4 T cell counts were also associated with hypertension in European [35] and African [34•] PWH, a finding specific to HIV populations. In addition to HIVrelated inflammation and detrimental effects of ART on adipocyte health and lipid metabolism, specific components of the virus such as the negative factor (Nef) protein, transcription protein (Tat), and glycoprotein 120 may contribute to the link between MetS and hypertension in PWH, perhaps superimposed on individual genetic predisposition [36][37][38].…”
Section: Role Of Hypertensionmentioning
confidence: 99%
“…The introduction and subsequent scaling up of highly active antiretroviral therapy HAART coverage has remarkably reduced HIV associated morbidity and mortality and increased the life expectancy of people living with HIV (PLWH). However, this gain seems to be counteracted by the rising incidence of hypertension among this PLWH [2]. Furthermore, contributing to this trend is the phenomenon of epidemiologic transition.…”
Section: Introductionmentioning
confidence: 95%
“…Globally, there is a growing trend of cardiovascular outcomes and metabolic complications in the HIV infected population. Accounting for 10% of non-AIDs related mortality, CVD are a major cause of morbidity and mortality amongst HIV subjects [2]. The lifelong CVD risk that trails HIV infection provides the premise for such study [5].…”
Section: Introductionmentioning
confidence: 99%